2001
DOI: 10.1046/j.1523-1755.2001.00481.x
|View full text |Cite
|
Sign up to set email alerts
|

Sulfate homeostasis, NaSi-1 cotransporter, and SAT-1 exchanger expression in chronic renal failure in rats

Abstract: These results demonstrate that both NaSi-1 and Sat-1 total protein abundances are decreased in CRF, which may contribute to the increase in fractional sulfate excretion. Strikingly, NaSi-1 density was not decreased in CRF three weeks after Nx, and furthermore, increased six weeks after Nx, in contrast to NaPi-2 density, which was decreased at both times. The significance of this difference remains to be determined, but may explain why hypersulfatemia occurs earlier than hyperphosphatemia in CRF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 33 publications
2
14
0
Order By: Relevance
“…During CRF, the expression of renal Sat-1 is signifi cantly reduced, which means that the active excretion of oxalate via the proximal tubule is also impaired. In addition, NaS-1, an important supplier of intracellular SO 4 2-for Sat-1-mediated oxalate transport, is also downregulated (156) (Figure 5.). 4 2-co-transport, mediated by the apical NaSi-1 (SLC13A1), which creates an outward SO 4 2-gradient that drives Sat-1-mediated SO 4 2-/oxalate exchange across the BLM.…”
Section: Figure 3 Transporters Along the Rodent Gastrointestinal Tracmentioning
confidence: 98%
“…During CRF, the expression of renal Sat-1 is signifi cantly reduced, which means that the active excretion of oxalate via the proximal tubule is also impaired. In addition, NaS-1, an important supplier of intracellular SO 4 2-for Sat-1-mediated oxalate transport, is also downregulated (156) (Figure 5.). 4 2-co-transport, mediated by the apical NaSi-1 (SLC13A1), which creates an outward SO 4 2-gradient that drives Sat-1-mediated SO 4 2-/oxalate exchange across the BLM.…”
Section: Figure 3 Transporters Along the Rodent Gastrointestinal Tracmentioning
confidence: 98%
“…NaS1 mRNA and protein levels are down-regulated in the renal cortex by a variety of conditions, including: high sulfate diet (Markovich et al 1998), hypothyroidism (Sagawa et al 1999b), vitamin D depletion (Fernandes et al 1997), glucocorticoids (Lee et al 2000b), hypokalemia (Markovich et al 1999a), metabolic acidosis (Puttaparthi et al 1999) and non-steroidal anti-inflammatory drugs (Sagawa et al 1998a), and upregulated by low sulfate diet (Sagawa et al 1998b), thyroid hormone (Sagawa et al 1999b), vitamin D supplementation (Fernandes et al 1997), growth hormone (Sagawa et al 1999a), chronic renal failure (Fernandes et al 2001) and during post-natal growth (Markovich et al 1999b). NaS1 promoter studies showed up-regulation by vitamin D, thyroid hormone and the xenobiotic 3-methycholanthrene (Dawson and Markovich 2002;Lee et al 2005;Lee and Markovich 2004) and down-regulated by glucocorticoids (Beck and Markovich 2000).…”
Section: Cloning and Functional Characterization Of Renal Sulfate Tramentioning
confidence: 99%
“…This reabsorption is mediated by Na + -dependent (NaSi-1) and Na + -independent processes (anion exchangers, such as CFEX/Slc26a6 and Slc26a7) at the brush-border and by sat-1 at the basolateral membrane [17,[31][32][33][34]37]. The physiological importance of the sat-1-mediated sulfate reabsorption has been confirmed in experimental chronic renal failure, which is associated with major downregulation of the renal sat-1 expression and significant increase of the fractional sulfate excretion [12].…”
Section: Introductionmentioning
confidence: 98%